2009
DOI: 10.1177/1938640009346449
|View full text |Cite
|
Sign up to set email alerts
|

Positional Effects of the Knee and Ankle on the Ends of Acute Achilles Tendon Ruptures

Abstract: Conservative management of acute Achilles tendon ruptures in a plantarflexed short leg cast or functional brace is a viable alternative to surgery. The ideal plantarflexion angle to allow the free ends of the tendon to oppose one another has not been clearly defined. The purpose of this cadaveric study was to define a plantarflexion angle where the free Achilles tendon ends reliably oppose one another. Ten cadaveric legs amputated at the distal femur were obtained. A laceration of the Achilles tendon was made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In contrast, other studies denote the importance of the specific postoperative casting regime [32]. Besides the length of the application period of the cast, the ankle angle is one important parameter [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies denote the importance of the specific postoperative casting regime [32]. Besides the length of the application period of the cast, the ankle angle is one important parameter [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Hence, different antiadhesion strategies to improve the gliding capability of the regenerating tendon are being developed [4]. First of all, the postoperative treatment has to be optimized with respect to its impact on the adhesion extent as it is well known that for example in Achilles tendon regeneration the ankle angle plays a crucial role [5]. Secondly, physical antiadhesion barriers consisting of biomaterials such as fibronectin [6], collagen [3], or silk [7] have been reported to show positive effects with respect to reducing adhesion formation.…”
Section: Introductionmentioning
confidence: 99%
“…Sekiya, et al [24] and Wray, et al [25] have demonstrated in cadaveric studies that knee flexion position does not influence the separation of the tendo Achilles ends while the plantarflexion position of the ankle does significantly affect the separation of the tendoachilles ends. Wray, et al [25] also showed that the ankle needs to be in at least 28 degrees of plantarflexion for the two ruptured ends of the tendoachilles to meet. Therefore the only factor to be controlled is the ankle position, which can be controlled in a below knee cast and an above knee cast is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Two cadaveric studies have examined and supported this principle with regards to the position of the knee. 3,18 In a study of six fresh frozen cadaveric Achilles tendons, measurement of the tendon gap with the knee and ankle in varying positions was made. The study showed that maximal independent reduction in tendon gap was achieved by plantarflexing the foot, with apposition of the tendon ends at 60 degrees plantarflexion and a mean gap of 20 mm with the ankle in neutral.…”
Section: Introductionmentioning
confidence: 99%
“…Complete tendon apposition was shown to occur at 28.0 degrees (95% confidence interval 25.0 to 33.6 degrees) regardless of the position of the knee. 18 There is no published evidence to show whether tendon gap changes with the position of the knee in the physiological environment of an acute rupture. Thus, the question remains whether in the conservative treatment of an acute Achilles tendon rupture, with the ankle in plantarflexion the knee should also be immobilized in a flexed position.…”
Section: Introductionmentioning
confidence: 99%